1995
DOI: 10.1002/etc.5620140605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactant addition on phenanthrene biodegradation in sediments

Abstract: A laboratory study was conducted to determine whether commercial surfactants enhance the bioremediation of PAH‐contaminated sediments. Phenanthrene was chosen as a representative PAH; an inoculum of PAH‐degrading microorganisms, enriched from an aquatic sediment, was used in sediment‐water slurry microcosm biodegradation experiments. Of seven nonionic surfactants tested, only one (Triton X‐100) did not inhibit phenanthrene mineralization at concentrations above the critical micelle concentration (CMC). Tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 32 publications
0
38
1
Order By: Relevance
“…In the case of microorganisms degrading hydrophobic hydrocarbons, the presence of surfactants, especially in concentrations above the CMC, has had an inhibiting effect [24][25][26]. Although this phenomenon may be partly explained by the reduced availability of micellar hydrocarbons [27,28], inhibition was also observed for hydrophilic substrates.…”
Section: Introductionmentioning
confidence: 91%
“…In the case of microorganisms degrading hydrophobic hydrocarbons, the presence of surfactants, especially in concentrations above the CMC, has had an inhibiting effect [24][25][26]. Although this phenomenon may be partly explained by the reduced availability of micellar hydrocarbons [27,28], inhibition was also observed for hydrophilic substrates.…”
Section: Introductionmentioning
confidence: 91%
“…A few studies have also indicated the potential for using micellar solubilization to clean up residual and sorbed contaminants from soils [10][11][12][13][14]. Surfactant may also improve microbial remediation of HOCs in soils by affecting the accessibility of the HOCs to microorganisms [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Many microorganisms, including bacteria, algae, and fungi, have been shown to possess degradative enzymes for the oxidative degradation of PAHs [34], however, the in situ microbial degradation of PAHs is limited by their low bioavailability. Various surfactants have been employed with attempts to increase the aqueous-phase concentrations of PAHs, and thus the bioavailability [4,8,17,18]. Removal of PAHs from contaminated soils and groundwater by surfactants is governed mainly by the micelle and/or microemulsion concentrations of surfactants to solubilize or mobilize the pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…In general, surfactants can increase the solubility of PAHs in the culture medium to increase their bioavailability. Studies have been reported that surfactants can enhance biodegradation percentage (Arosetin and Alexander 1992;Thiem 1994), while others have found that applying surfactants inhibits biodegradation due to the alteration of the interactions between the cells and the substrate (Stelmack et al 1999) or the toxicity of surfactants themselves (Colores et al 2000;Tsomides et al 1995;Volkering et al 1995;Kawai et al 1997). It was observed from our experiments that surfactants could enhance the solution of BaP, but they did not improve the degradation percentage of BaP.…”
Section: Affecting Factors Of Bap-degradation By Strain Bap14mentioning
confidence: 96%